The orientation towards adopting international public accounting standards and its role in enhancing transparency and combating administrative and financial corruption in Algeria (Journal of Economic Additions, 2020)
This research paper aims to identify international general accounting standards as one of the important tools in combating financial and administrative corruption in Algeria one of the effective means that can be adopted in Algeria.The study concluded that the public accounting system in Algeria still suffers from several imbalances, , Especially as it relies on a system based on monetary basis , Despite international developments in this regard, and the tendency of many countries to adopt international accounting standards in the public sector, Although the requirements of adapting the Algerian public accounting system to international standards have been completed, However, it was not materialized on the ground for many reasons, This delay, which leads to bad effects, especially with regard to transparency and accountability, Which made it suffer from financial and administrative corruption.Keywords: public accounting, international accounting standards, financial and administrative corruption, Algeria.Jel Classification Codes: M49 . H59. P43